ANALISIS TINGKAT BERPIKIR KREATIF SISWA GAYA BELAJAR VISUAL DALAM MEMECAHKAN MASALAH PERSEGI PANJANG DAN PERSEGI - Sunardi, Sunardi; Ramadhani, Amalia Febrianti; Oktavianingtyas, Ervin (Kadikma, 2017)
Abstract. This study aims to describe the level of students' creative thinking in visual learning style in solving rectangular and square problems. The type of this research is descriptive research with qualitative approach. Data collection method used was questionnaire method, test method and interview method. The subjects of the study were the students of visual learning style in grade VIII-D SMP Negeri 1 Jember which amounted to 12 students. The degree of students' creative thinking was classified into five, namely TBK 4 (very creative), TBK 3 (creative), TBK 2 (quaite creative), TBK 1 (less creative) and TBK 0 (not creative) where the division of creative thinking based on reference levels of fluency, flexibility, and novelty. The validation analysis calculation based on problem-solving tests, obtained Va = 2.94 and validation analysis guidelines for the calculation of the interview, obtained Va = 2.58. The results showed that 4 students with TBK 4 qualified all creative thinking criteria that included fluency, flexibility, and novelty. 4 students with TBK 3 qualified two creative thinking criteria with details of a student qualified the fluency and novelty criteria, and 3 students qualified the criteria of fluency and flexibility. 2 students with TBK 2 qualified the criteria of flexibility. 1 student with TBK 1 qualified the fluency criteria. 1 student with TBK 0 did not qualify any criteria of creative thinking be it eloquence, flexibility, or novelty. Keywords: Degree of Creative Thinking, Visual Learning Style, Problem Solving